When God Is “Weak”: Divine Will in the Framework of Javanese Ethics and Caputo’s Thought - Putrawan, Bobby Kurnia (Theology today, 2026)
This article explores the concept of “divine will” in the context of Javanese ethics and John D. Caputo's philosophical thought on “theology of the event.” The article argues that weakness, often understood as lack, is the key to understanding the manifestation of divine will. In Javanese ethics, the concept of “nrima” reflects the acceptance of divine will that often comes through uncertainty and suffering. Meanwhile, Caputo, through his reading of Derrida, deconstructs the concept of an omnipotent and omnipresent God into a God who is present through unexpected and uncontrollable “events.” In this frame of thought, weakness is understood as a space open to surprise and wonder, a place where the divine will reveals itself. This article seeks to find common ground between Javanese ethics and Caputo's thinking in understanding the meaning of “divine will” in a world full of uncertainties. The contribution of this article is to provide a new perspective in discussing the problem of theodicy by focusing on the positive meaning of weakness and uncertainty in understanding God's actions.